Absolute incomprehensibility - Buda, Stanisław (Hybris, 2015)
The author attempts to rethink the philosophical problem of "absolute incomprehensibility". The problem arises in connection with a quest for the possibility of a final and absolute consolidation of sources and reasons of everything that aspires to have sense, that is, in connection with the question of reasonableness itself. The key issue proves to be relationships of categories like: absolute, reality, man and philosophizing. All this requires serious metaphysical settlements. In the final conclusions the author postulates the complementation of apophatic theology and apophatic anthropology.